Characterization of Near Full-Length Transmitted/Founder HIV-1 Subtype D and A/D Recombinant Genomes in a Heterosexual Ugandan Population (2006–2011) - Sheila N. Balinda; Anne Kapaata; Rui Xu; Maria G. Salazar; Allison T. Mezzell; Qianhong Qin; Kimberly Herard; Dario Dilernia; Anatoli Kamali; Eugene Ruzagira; Freddie M. Kibengo; Heeyah Song; et al. (Viruses, 2022)
Detailed characterization of transmitted HIV-1 variants in Uganda is fundamentally important to inform vaccine design, yet studies on the transmitted full-length strains of subtype D viruses are limited. Here, we amplified single genomes and characterized viruses, some of which were previously classified as subtype D by sub-genomic pol sequencing that were transmitted in Uganda between December 2006 to June 2011. Analysis of 5′ and 3′ half genome sequences showed 73% (19/26) of infections involved single virus transmissions, whereas 27% (7/26) of infections involved multiple variant transmissions based on predictions of a model of random virus evolution. Subtype analysis of inferred transmitted/founder viruses showed a high transmission rate of inter-subtype recombinants (69%, 20/29) involving mainly A1/D, while pure subtype D variants accounted for one-third of infections (31%, 9/29). Recombination patterns included a predominance of subtype D in the gag/pol region and a highly recombinogenic envelope gene. The signal peptide-C1 region and gp41 transmembrane domain (Tat2/Rev2 flanking region) were hotspots for A1/D recombination events. Analysis of a panel of 14 transmitted/founder molecular clones showed no difference in replication capacity between subtype D viruses (n = 3) and inter-subtype mosaic recombinants (n = 11). However, individuals infected with high replication capacity viruses had a faster CD4 T cell loss. The high transmission rate of unique inter-subtype recombinants is striking and emphasizes the extraordinary challenge for vaccine design and, in particular, for the highly variable and recombinogenic envelope gene, which is targeted by rational designs aimed to elicit broadly neutralizing antibodies.